Challenges regarding MR compatibility of an MRgFUS robotic system - Antoniou, Anastasia; Georgiou, Leonidas; Evripidou, Nikolas; Ioannides, Cleanthis; Damianou, Christakis A. (My University, 2022)
Numerous challenges are faced when employing Magnetic Resonance guided Focused Ultrasound (MRgFUS) hardware in the Magnetic Resonance Imaging (MRI) setting. The current study aimed to provide insights on this topic through a series of experiments performed in the framework of evaluating the MRI compatibility of an MRgFUS robotic device. All experiments were performed in a 1.5 T MRI scanner. The main metric for MRI compatibility assessment was the signal to noise ratio (SNR). Measurements were carried out in a tissue mimicking phantom and freshly excised pork tissue under various activation states of the system. In the effort to minimize magnetic interference and image distortion, various set-up parameters were examined. Significant SNR degradation and image distortion occurred when the FUS transducer was activated mainly owing to FUS-induced target and coil vibrations and was getting worse as the output power was increased. Proper design and stable positioning of the imaged phantom play a critical role in reducing these vibrations. Moreover, isolation of the phantom from the imaging coil was proven essential for avoiding FUS-induced vibrations from being transferred to the coil during sonication and resulted in a more than 3-fold increase in SNR. The use of a multi-channel coil increased the SNR by up to 50 % compared to a single-channel coil. Placement of the electronics outside the coil detection area increased the SNR by about 65 %. A similar SNR improvement was observed when the encoders' counting pulses were deactivated. Overall, this study raises awareness about major challenges regarding operation of an MRgFUS system in the MRI environment and proposes simple measures that could mitigate the impact of noise sources so that the monitoring value of MR imaging in FUS applications is not compromised.
Keywords: Artifacts; MRI compatibility; MRgFUS; Robotic device; SNR